EVALUATING ASSOCIATION OF TRAUMATIC BRAIN INJURIES IN PATIENTS PRESENTING WITH MAXILLOFACIAL FRACTURES: AN INSIGHT FROM LADY READING HOSPITAL, KPK - AFSAR, H; HAYAT, M; ULLAH , U; SHAH , Z; HUSSAIN , K (Biological and Clinical Sciences Research Journal, 2024)
WHO recognized Traumatic brain injury (TBI) is a major global contributor to mortality, impacting over 50 million people annually.2 Traumatic brain injuries often accompany maxillofacial fractures due to their close proximity and may present with or without neurological symptoms. Objective: This study aims to evaluate indicators of traumatic brain injury and its severity in conjunction with maxillofacial fractures. Methods: This descriptive study was conducted at Oral and Maxillofacial Surgical Department of Lady Reading Hospital, KPK. A non-probability, consecutive sampling technique was used to gather a sample of 184 participants (95% confidence interval and a 5% margin of error, population 0.8).8 Patient’s aged 10-60 who presented with traumatic brain injury along with maxillofacial fractures were included in study. Patients with pre-existing neurological disorders were excluded from the study. Data was collected in a specified Performa and was analyzed using SPSS 22. Results: The mean age group recorded was 21.46 ±13.2. The ratio of males to females was 3:1. The most common traumatic brain injury was amnesia (38%), followed by an altered level of consciousness (37. 1%).The most common mechanism of trauma was Road Traffic Accidents (70.6%) followed by falls (16. 8%).combination of ZMC, Mid-facial and mandibular fractures (panfacial) was most common type of maxillofacial trauma (55%). There was a statistically significant association for TBI along with Facial fractures (P=0.001).Conclusion: Traumatic brain injuries in patients with maxillofacial trauma are life-threatening, requiring early detection to enhance survival and recovery. A multidisciplinary approach, involving maxillofacial surgeons and neurosurgeons, is essential for effective management.